2012
DOI: 10.1002/jmri.23811
|View full text |Cite
|
Sign up to set email alerts
|

T2* MRI of minimal hepatic encephalopathy and cognitive correlates in vivo

Abstract: Decreased phase values in the frontal cortical-basal ganglial circuits independently contribute to cognitive impairments in MHE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
(15 reference statements)
1
17
1
Order By: Relevance
“…Susceptibility weighted phase imaging had been used to quantify brain iron content in healthy population [22], [27] and in patients with Parkinson’s disease, Alzheimer’s disease or multiple sclerosis [25], [36], [37]. We reported that patients with HBV-related hepatic cirrhosis had excessive brain iron accumulation in the basal ganglia, which was consistent with our previous research [16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Susceptibility weighted phase imaging had been used to quantify brain iron content in healthy population [22], [27] and in patients with Parkinson’s disease, Alzheimer’s disease or multiple sclerosis [25], [36], [37]. We reported that patients with HBV-related hepatic cirrhosis had excessive brain iron accumulation in the basal ganglia, which was consistent with our previous research [16].…”
Section: Discussionsupporting
confidence: 90%
“…Excessive brain iron deposition was found in Parkinson’s disease [10], Alzheimer’s disease [11], multiple sclerosis [12], Friedreich’s ataxias [13], neuroferritinopathy [14], and Hallervorden-Spatz syndrome [15]. Our previous study revealed that excessive iron accumulation in the frontal cortical-basal ganglial circuit independently contributed to cognitive impairments in minimal hepatic encephalopathy patients [16]. However, the underlying mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 96%
“…A whole class of diseases termed neurodegeneration with brain iron accumulation (NBIA), for example, are exclusively diagnosed by abnormal high concentrations, typically in the basal ganglia and many with psychomotor symptoms beginning in earlier life (Schipper, 2012; Gregory and Hayflick, 2014). Other iron-dependent diseases, such as hematic encephalopathy associated with cirrhosis of the liver, also present with abnormal brain iron content and associated cognitive deficits (Liu et al, 2013; Xia et al, 2015). …”
Section: Brain Iron In Neurodegenerative Disordersmentioning
confidence: 99%
“…Abnormalities in the iron and manganese of the brain have been suggested as possible metabolic sources of the neurological manifestations of chronic hepatic dysfunction, including in liver cirrhosis patients . Given that the liver is a central organ for the metabolism of the two metals and that the places iron and manganese are commonly deposited overlap, such as in the GP, we postulated an interaction between iron and manganese in the brains of advanced liver cirrhosis patients.…”
mentioning
confidence: 95%